(3CHjGJ aj GdMOjK Ydi ESJNQGL Chdg eYQag Gddg JYGdi GdYbdjI ef cJGHI GdcQjes - (3YdGA GdOjf Hf eMeO Hf EHQGgje GdhRjQs; (3TeS GdOjf CHh YHO Gddg eMeO Hf CHj HcQ Hf CjhH Hf bje GdLhRjg, GHf Gdbje,J (B751 (3g` s ((3eMeO Hf ESeGYjd GdCejQ s)
(3ChdgG (B:s
(3CUhd Ojfi cJGH Gddg dG GdYQV hdjg di ai CUhd ZjQ ZQV s
(3BNQgG (B:s
(3JUdi HgG ZjQ eCLhQjfG QCSi hbhOgG GdbdH hGdCacGQ JYQV Ke GdUdGg Ydi ef ai edGReJi dbhdg GdMb Yf ef dGefi YhV EfJgJ hddg GdMeO hGdUdGI hGdSdGe Ydi eMeO hBdg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B56s
Keywords: (3GdeLGejYs